EFFECT OF VACUUM FRYING TEMPERATURE ON THE PHYSICOCHEMICAL AND SENSORY PROPERTIES OF CHAYOTE CHIPS - Rahman, Abdul; Ismed, Ismed; Aisman, Aisman (Institute of Computer Science (IOCS), 2025)
Chayote (Sechium edule) is a high-moisture vegetable with considerable potential for development into value-added snack products through vacuum frying technology. This study aimed to evaluate the effect of vacuum frying temperature on the physicochemical, nutritional, and sensory properties of chayote chips in order to determine the optimal processing condition. Fresh chayote was first characterized for its initial chemical composition and subsequently vacuum-fried at five temperature levels. This study uses a Completely Randomized Design (CRD) with five treatments and three replications. The treatments consist of frying temperatures of 70°C (A), 75°C (B), 80°C (C), 85°C (D), and 90°C (E). The resulting chips were analyzed for yield, texture, color, frying time, oil absorption, proximate composition, vitamin C content, potassium concentration, and sensory attributes. The data were analyzed using analysis of variance (ANOVA), followed by Duncan’s New Multiple Range Test (DNMRT). Increasing frying temperature significantly reduced yield, moisture content, hardness, and frying time, while increasing oil absorption and relative mineral concentration. Nutritional analysis revealed progressive degradation of heat-sensitive components, particularly protein and vitamin C, at higher temperatures. Sensory evaluation revealed that frying temperature significantly influenced aroma, taste, and texture attributes, with the highest aroma score (4.10), taste score (4.13), and texture score (4.37 for crispiness) observed at 85 °C. Overall, vacuum frying temperature played a critical role in determining product quality, highlighting a trade-off between processing efficiency, nutritional retention, and sensory acceptance. Frying at 85 °C under vacuum conditions was identified as the optimal temperature for producing chayote chips with desirable physical characteristics, acceptable nutritional quality, and superior consumer acceptance.